2018
DOI: 10.1007/s12031-018-1156-5
|View full text |Cite
|
Sign up to set email alerts
|

The Heptahelical Domain of the Sweet Taste Receptor T1R2 Is a New Allosteric Binding Site for the Sweet Taste Modulator Amiloride That Modulates Sweet Taste in a Species-Dependent Manner

Abstract: The activity of sweet taste receptor (heterodimeric T1R2 and T1R3) can be modulated by sweet regulators. The compound amiloride can inhibit the sweet sensitivity of the human sweet taste receptor. This study describes the species-dependent regulation of the response of sweet taste receptors by this sweet inhibitor. Amiloride inhibited the sweet taste response of humans and mice but not that of squirrel monkeys. Using human/squirrel monkey/mouse chimeric T1R2 and T1R3 receptors as well as the agonist perillarti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…To characterize the interactions of purified hTAS1R2 with its ligands, we determined the dose–response relationship of its intrinsic tryptophan fluorescence upon titration with sweeteners previously demonstrated to bind the hTAS1R2 subunit 3 , 10 12 , 15 , 16 , 26 , 28 . We first tested the ability of neotame, sucralose, and acesulfame-K to bind to hTAS1R2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To characterize the interactions of purified hTAS1R2 with its ligands, we determined the dose–response relationship of its intrinsic tryptophan fluorescence upon titration with sweeteners previously demonstrated to bind the hTAS1R2 subunit 3 , 10 12 , 15 , 16 , 26 , 28 . We first tested the ability of neotame, sucralose, and acesulfame-K to bind to hTAS1R2.…”
Section: Resultsmentioning
confidence: 99%
“…8 A,C,D). We also tested the sweetener perillartine shown to activate the monomeric hTAS1R2 receptor and bind its TMD 26 28 . We found that perillartine interacts with hTAS1R2 with lower affinity leading to a K d value of 373 ± 110 µM (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although TMDs of TAS1R3 are the most likely regions responsible for allosteric modulation, TMDs and VFT regions of TAS1R2 cannot be ruled out completely. For example, the diuretic amiloride binds to TAS1R2 (TMD3, TMD5, TMD7) and inhibits the sweet response in a species dependent manner (Zhao et al, 2018). Further, the umami compound [monosodium glutamate (MSG)] and peptides (Glu-Asp, Glu-Glu) bind to the VFT region of TAS1R2 and inhibit the sweet induced response (Shim et al, 2015).…”
Section: Negative Allosteric Modulation Of Sweet Receptormentioning
confidence: 99%
“…Amiloride inhibited the response of perillartine as a sweet activator on hT1R2/T1R3, T1R2, and T1R2‐heptahelical domain (HD). Molecular modeling suggested that perillartine and amiloride occupy the same binding pocket on the extracellular side of the hT1R2‐HD …”
Section: T1r2/t1r3 Receptorsmentioning
confidence: 99%